Comparison of EMG amplitudes recorded by ipsilateral and contralateral electrodes placement during using trans-thyroid cartilage recording method in thyroid surgery - Chiang, Feng-Yu; Shih, Yu-Chen; Lien, Ching-Feng; Wang, Chih-Chun; Wang, Chien-Chung; Hwang, Tzer-Zen; Huang, Yaw-Chang; Wu, Che-Wei; Yeh, Tai-Hung; Huang, Tzu-Yen (Frontiers in Endocrinology, 2024)
Objectives: The feasibility and reliability of trans-thyroid cartilage EMG recording method (TCERM) during intraoperative monitoring (IONM) of the recurrent laryngeal nerve (RLN) in thyroid surgery have been established. This study compared two different recording electrode placements on the ipsi-lateral and contra-lateral lamina of the thyroid cartilage (TC). Methods: Fifty consecutive patients undergoing total thyroidectomy with 100 RLNs at risk were enrolled. Two paired subdermal needle electrodes were inserted into the subperichondrium of the bilateral TC lamina to record electromyography (EMG) signals. The channel leads from the TC electrodes were connected to the patient interface with two different modes. In A-mode, the electrode leads were placed ipsi-laterally, and channel 1 monitored the left RLN and channel 2 monitored the right RLN respectively. In B-mode, the electrode leads were placed contra-laterally, and channels 1 and 2 simultaneously monitored the same side of the RLN. The amplitudes of four EMG signals (V1-R1-R2-V2) recorded by A-mode and B-mode were compared. Results: All EMG amplitudes of V1-R1-R2-V2 signals recorded with B-mode were all above 500μV and significantly higher than those with A-mode (p<0.001). No false loss of signal, electrode dislodgement, or needle-related complications were noted during IONM. Postoperatively, all patients had symmetrical vocal cord movement. Lower EMG amplitudes were observed in older and male patients. Histopathology and laterality showed no significant differences in EMG amplitude. Conclusion: During using TCERM in thyroid surgery, the recording electrodes should be placed contra-laterally on the TC lamina. This approach ensures high and stable EMG signals, which are important for high-quality IONM of the RLN.